Spatial interpolation of daily humidity using natural neighbours over mountain areas in south eastern Australia - Kim, K.S.; Beresford, R.M.; Henshall, W.R. (New Zealand Plant Protection, 2008)
Natural neighbour interpolation was investigated to estimate daily humidity at specific sites in a mountain area The Global Summary of Day (GSOD) dataset was used to obtain weather data in mountain areas in south eastern Australia Eighteen weather stations were selected as validation sites Dew point temperature was estimated from January to December 2007 When the inverse distance weight method was used without adjusting the elevation difference between stations accuracy of virtual dew point temperature was poor with a mean absolute error (MAE) of 36C When natural neighbour interpolation was used the MAE for dew point temperature was 21C with altitude adjustment Furthermore application of wet adiabatic lapse rate (0004C/m) for altitude adjustment reduced the MAE to 13C These results will be used to improve the accuracy of weather estimates in areas with complex terrain in order to implement crop disease predictions using risk models